Understanding Asian corporate management: a global comparative framework - Grainger, Richard; Chatterjee, Samir Ranjan (The Haworth Press Inc., 2008)
Asia is now set to rival the West in economic terms, and an understanding of Asian management is critical. General interest in this area has its origins in the Japanese economic miracle, regional influence of the overseas Chinese, and the contemporary emergence of China and India. Although “Asian management” is established as a subdiscipline of international management, there are few standardized frameworks. This article explores and recommends a descriptive, comparative approach to understanding Asian management that recognizes global and local imperatives. Two illustrative case studies of major Asian corporations are offered in illustration of the utility of the framework.